Biodiversity in Enclosed Seas and Artificial Marine Habitats
DOI: 10.1007/978-1-4020-6156-1_17
|View full text |Cite
|
Sign up to set email alerts
|

History, ecology and trends for artificial reefs of the Ligurian sea, Italy

Abstract: From 1970 to the present 10 artificial reef sites have been developed in coastal waters of the Ligurian Sea, Italy. They range from Ventimiglia, in the west, to La Spezia, in the east, with the largest and best known reef complex being located in the Gulf of Genoa at Loano and consisting of 2,745 m 3 , about 5,200 t of material and covering a surface of 350 ha. Design and construction prac-Keywords

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…Relini et al (2007) showed in Liguria that wooden barges and shipwrecks were less appropriate for colonization, in agreement with video shot on the Cycnus. Iron structures of wrecks are usually damaged by corrosion, which first attacks the thinnest parts (Relini et al, 2007) and at the end, may contribute to the collapse of the whole structure (Bell et al, 1997). This damage is enhanced by bubbles emitted by SCUBA opencircuit apparatus and by chains used to anchor diving buoys.…”
Section: Figuresupporting
confidence: 81%
See 3 more Smart Citations
“…Relini et al (2007) showed in Liguria that wooden barges and shipwrecks were less appropriate for colonization, in agreement with video shot on the Cycnus. Iron structures of wrecks are usually damaged by corrosion, which first attacks the thinnest parts (Relini et al, 2007) and at the end, may contribute to the collapse of the whole structure (Bell et al, 1997). This damage is enhanced by bubbles emitted by SCUBA opencircuit apparatus and by chains used to anchor diving buoys.…”
Section: Figuresupporting
confidence: 81%
“…Experiments comparing natural habitats and artificial substrata such as concrete, rocks, ceramic, and earthenware material demonstrated that species recruitment and survival were strictly dependent on the substrate-type (Burt et al, 2009;Antoniadou et al, 2010). Relini et al (2007) showed in Liguria that wooden barges and shipwrecks were less appropriate for colonization, in agreement with video shot on the Cycnus. Iron structures of wrecks are usually damaged by corrosion, which first attacks the thinnest parts (Relini et al, 2007) and at the end, may contribute to the collapse of the whole structure (Bell et al, 1997).…”
Section: Figurementioning
confidence: 50%
See 2 more Smart Citations
“…Few studies on artificial reefs, however, have addressed temporal changes of fishes attracted over extended (i.e. a decade or more) periods (Spanier, ; Relini et al., , ; Baine and Side, ; Santos and Monteiro, ; Santos et al., ). Consequently, fishery resource variations with the age of an artificial reef are barely known, especially in the Neotropics, despite their potential to improve inshore artisanal fisheries in the overall low productivity of Brazilian coastal waters (Amaral and Jablonski, ).…”
Section: Introductionmentioning
confidence: 99%